2014
DOI: 10.18632/oncotarget.2944
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 1 gene amplification is associated with poor survival in patients with resected esophageal squamous cell carcinoma

Abstract: To investigate the frequency and the prognostic impact of fibroblast growth factor receptor 1 (FGFR1) gene amplification in 526 curatively resected esophageal squamous cell carcinoma (ESCC). Using fluorescent in situ hybridization, high amplification was defined by an FGFR1/centromer 8 ratio is ≥ 2.0, or average number of FGFR1 signals/tumor cell nucleus ≥ 6.0, or percentage of tumor cells containing ≥ 15 FGFR1 signals or large cluster in ≥ 10%. Low amplification was defined by ≥ 5 FGFR1 signals in ≥ 50%. FGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 36 publications
5
35
1
Order By: Relevance
“…FGFR1 gene amplification was observed in about 12% tested hypopharyngeal and laryngeal SCC cases that was slightly more frequent in hypopharyngeal SCC (14.3%) Variables of the pT and pN classification were not included in the multivariate analysis, because they were included in the pathologic stage than in laryngeal SCC (8.3%). FGFR1 amplification has been suggested as an oncogenic driver mutation in tobacco-associated cancers of the aerodigestive tract [16,[32][33][34]. Previous studies on FGFR1 in HNSCC have shown that FGFR1 amplification is more common in the SCC of hypopharynx and larynx than in that of oropharynx or oral cavity [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 gene amplification was observed in about 12% tested hypopharyngeal and laryngeal SCC cases that was slightly more frequent in hypopharyngeal SCC (14.3%) Variables of the pT and pN classification were not included in the multivariate analysis, because they were included in the pathologic stage than in laryngeal SCC (8.3%). FGFR1 amplification has been suggested as an oncogenic driver mutation in tobacco-associated cancers of the aerodigestive tract [16,[32][33][34]. Previous studies on FGFR1 in HNSCC have shown that FGFR1 amplification is more common in the SCC of hypopharynx and larynx than in that of oropharynx or oral cavity [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 protein expression of ≥1% in tumors was associated with poor survival in patients with breast cancer [35]. FGFR1 amplification was also associated with poor survival in esophageal cancer [36], breast cancer [37], and squamous-cell lung cancer [38]. In a study of colorectal cancer, the copy number gain of FGFR1 significantly correlated with worse outcomes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported the prognostic implication of FGFR1 amplification in ESCC, but the results were controversial[11,12]. FGFR1 amplification was associated with poor prognosis or had no prognostic significance in ESCC; however, the FISH criteria for FGFR1 amplification were not identical[11,12].…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 amplification was associated with poor prognosis or had no prognostic significance in ESCC; however, the FISH criteria for FGFR1 amplification were not identical[11,12]. In the present study, FGFR1 amplification was a favorable prognostic indicator in patients with resected ESCC, which was in conflict with a previous report using the same FISH criteria[11]. In a study using FISH and different criteria, FGFR1 amplification was not associated with clinical outcomes in patients with ESCC[12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation